Orbital Plates and Screws Causing Globe Fixation: A Rare and Delayed Complication of Craniomaxillofacial Surgery. Issue 3 (May 2018) - Chandra, Varun; Buck, Danielle; Chakrabarti, Rahul; McNab, Alan
Abstract : A 24-year-old woman presented with a 1-year history of gradually increasing pain on eye movements, worse on the right. She had a significant background of undergoing intracranial correction of orbital hypertelorism with internal fixation of the lateral orbital rims at the age of 6 years. Imaging was consistent with bilateral metallic foreign bodies from both lateral orbital rims protruding into the globes. The patient underwent removal of bilateral plates and screws, with a significant improvement of symptoms and ocular motility postoperatively. This case demonstrates the need to consider orbital screw/plate migration in the setting of reduced ocular motility and painful eye movements. Abstract : A case of orbital plates and screws resulted in a delayed complication of globe fixation.